Cataloguing : - Mal, Bidyut (Shree, 2006)
Contents of material: Fundamentals of library cataloguing: An introduction. Cataloguing today. Cataloguing: The changing scenario. Major problems of cataloguing. Library standad. Towards future. organising for access. Glossary. Bibliography.